CHIP/Stub1 functions as a tumor suppressor and represses NF-?B-mediated signaling in colorectal cancer - Wang, Y.; Ren, F.; Wang, Y.; Feng, Y.; Wang, D.; Jia, B.; Qiu, Y.; Wang, S.; Yu, J.; Sung, J.; Xu, J.; Zeps, Nikolajs; et al. (Oxford University Press, 2014)
The carboxyl terminus of Hsc70-interacting protein (CHIP, also named Stub1), a U-box containing E3 ubiquitin ligase, is involved in degradation of certain oncogenic proteins. Recent studies indicated that CHIP suppresses tumor progression in human cancers by targeting Src-3, hypoxia inducible factor 1α, NF-κB, ErbB2 and c-Myc. Here, we report that CHIP was downregulated, predominantly, in the late stages of human colorectal cancer (CRC), and that the CHIP promoter was hypermethylated in CRC specimens. Overexpression of CHIP in HCT-116 cells resulted in impaired tumor growth in nude mice and decreased abilities of tumor cell migration and invasion. Conversely, depletion of CHIP in HCT-116 cells promoted tumor growth and increased tumor cell migration and invasion. CHIP was further found to negatively regulate NF-κB signaling in HCT-116 cells by promoting ubiquitination and degradation of p65, a subunit of the NF-κB complex. The suppressive effect of CHIP led to decreased expression of NF-κB-targeted oncogenes including Cyclin D1, c-Myc, MMP-2, VEGF and IL-8. We proposed that CHIP inhibits the malignancy of CRC cells, possibly through targeting NF-κB signaling. This study provides functional evidence for CHIP as a potential tumor suppressor in CRC, and CHIP expression may be a marker for stages of CRC.